Improving TPQ Teaching Skills In Optimizing Digital Media Learning Through The Canva Application - Rohmalina, Rohmalina; Huda, Miftahul; Masduki, Damayanti; Bawamenewi, Arozatulo; Abda, Muhammad Ichsan (Journal Of Human And Education (JAHE), 2024)
This article is the work of dedication carried out by the five authors in Almendah Village, West Java, Sri Mulyo Village, Malang Regency, Hilimbulawa Village, Nias, and Lamahu Bone Village. During his service to different villages, the author discovered a number of the same problems, namely physical infrastructure problems in the form of building siring, roads, bridges, and so on. However, this problem is not realistic to be resolved if you look at your financial capabilities and the time you have. The only problems that can be resolved are the monotonous learning methods of TPQ, the decreasing enthusiasm for learning of TPQ children, and the increasing number of TPQ children who use digital technology in a negative way, namely addiction to online games. For this reason, the author chose a solution to provide CANVA application training to PTQ teachers with the hope that these teachers will teach it to TPQ children. The aim is to make learning methods more varied, PTQ children are happy and enthusiastic about learning again, and can use technology. digital with positive things. The latest news that the author received was that this learning method was well received by PTQ children and the hope is that the children's enthusiasm will return and they will be able to use digital technology well.